Agile coaching for global software development. Issue 4 (13th December 2012) - Paasivaara, Maria; Lassenius, Casper
SUMMARY: This paper presents a case study on building a successful agile coaching team focusing on global software development projects in an international Nordic‐based software company. We describe how the team of eight coaches was built, and how the coaches work together as a team using agile practices, such as weekly iterations, backlogs, and daily stand‐ups. Furthermore, we describe their 'deep and narrow' approach to working closely with case projects, and the benefits to the coached projects. We describe the main challenges in building the coaching activities in a globally distributed company. The paper concludes with a set of lessons learned for coaching globally distributed projects and a discussion of the future plans for scaling up coaching by building a global coaching network within the company. We collected the data using 13 semi‐structured interviews of the coaching team members, and personnel from four coached case projects. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : This paper presents how a successful agile coaching team, focusing on global software development projects, was build, and how the coaches work as a team using agile practices, such as weekly iterations, backlogs, and daily stand‐ups. The paper describes their "deep‐and‐narrow" approach to working closely with projects, the benefits of coaching, the challenges of building coaching in a global company, the lessons learned for coaching global projects and the future plans for building a global coaching network.